Theory of the Unified Gravity: Sayed’s Quantum Gravity Force (SQGF) as a Function in Wavelength and Planck Length with Inevitability of Light Speed Violation (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Nothing by chance, everything was created by Allah (God). Quantum gravity (QG) is a hundred year unsolved puzzle and nagging mystery. This article introduces an innovative theory to describe quantum gravity by merging Newtonian, general relativity and quantum mechanics concepts. A unified formula and equations for quantifying and defining the quantum gravity was derived. It is called Sayed`s quantum gravity force (SQGF). It can be concluded that the gravity is a force inversely proportional to the square of the gravity quanta wavelength and distance; it is not only due to warping and curvature of the space-time fabric. The derived equation indicates that the gravity is also quantized. The Sayed`s gravitational constant (AsM) was given. The SQGF formula was validated and verified by check its units and calculations of the wavelengths in the micro and macroscopic scale. For the micro gravity force of 1µN (1 micro Newton), the wavelength was calculated. It was found to be in the measurable range of the electromagnetic spectrum. The quanta gravity wavelength of values 5.6026 x 10-9 m and 2.83457 x 10-13 m were found for Planck scale and electron-proton of H-atom respectively. A proposed approach to measure the relative gravity wavelengths is given. It can revolutionary be concluded that the speed of light is a variable. The violation of light speed is a must for the instantaneous nature of the gravity quanta and the entanglement phenomena.